Constrained Interactions and Social Coordination - Mathias Staudigl; Simon Weidenholzer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We consider a co-evolutionary model of social coordination and network formation where agents may decide on an action in a 2x2 - coordination game and on whom to establish costly links to. We fi nd that a payo ff dominant convention is selected for a wider parameter range when agents may only support a limited number of links as compared to a scenario where agents are not constrained in their linking choice. The main reason behind this result is that under constrained interactions agents face a trade-off between the links they have and those they would rather have.
Keywords: C73; C72; D85; 330